IMPLEMENTATION OF PROJECT BASED LEARNING MODELS TO IMPROVE MATHEMATICS LEARNING OUTCOMES IN CLASS IV SD STUDENTS - Firdaus Firdaus; Hana Cahyati; Huswatun Hasanah; Melinda Yanuar (Sean Institute, 2023)
In implementing mathematics learning in grade IV SD, there are still challenges that need to be overcome. Many students have difficulty understanding abstract mathematical concepts and are often difficult to apply in everyday life. The purpose of this research is to improve student learning outcomes through the application of the Project Based Learning learning model. This type of research is classroom action research which is carried out in 2 cycles where each cycle is carried out with 2 meetings. Data collection techniques using tests and non-tests. The data analysis technique used is descriptive comparative. Based on the results of the research, it shows that the application of the Project Based Learning model can improve the learning outcomes of fourth grade elementary school students. Suggestions for teachers are to use a project-based learning model as an alternative in overcoming student learning problems. This model has been proven effective in improving student learning outcomes. In addition, the use of project based learning can also be developed in other subjects. In addition, it can be an interesting research subject for further research